2011
DOI: 10.1111/j.1365-2966.2011.18723.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiative cooling functions for primordial molecules

Abstract: Cooling of primordial gas plays a crucial role in the birth of the first structures in our Universe. Due to the low fractional abundance of molecular species at high redshifts, spontaneous emission rather than collisions represents the most efficient way to cool the pristine plasma. In the present work, radiative cooling functions are evaluated for the diatomic species HD, HD$^+$, HeH$^+$, LiH and LiH$^+$. Cooling functions for the triatomic ions H$_3^+$ and H$_2$D$^+$ are also considered. Analytic fits as fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 41 publications
5
66
0
1
Order By: Relevance
“…The largest discrepancy for G ν between our calculations and the experiment is 2.47 cm −1 , which occurs for v = 22, while the largest difference for ΔG ν +1/2 is smaller at 1.85 cm −1 for v = 22. Some select transition energies are listed in Table 3 along with the corresponding experimental results of Dulick et al (1998) and the calculations of Coppola et al (2011). It can be seen that the current results are in excellent agreement with experiments, the largest discrepancy being 0.027 cm −1 .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The largest discrepancy for G ν between our calculations and the experiment is 2.47 cm −1 , which occurs for v = 22, while the largest difference for ΔG ν +1/2 is smaller at 1.85 cm −1 for v = 22. Some select transition energies are listed in Table 3 along with the corresponding experimental results of Dulick et al (1998) and the calculations of Coppola et al (2011). It can be seen that the current results are in excellent agreement with experiments, the largest discrepancy being 0.027 cm −1 .…”
Section: Resultssupporting
confidence: 68%
“…comm. ) and Coppola et al (2011), along with the low-density limit cooling function (n H ≤ 100 cm −3 ) due to H collisions (Galli & Palla 1998) (see the Appendix for a further discussion). All three LTE cooling functions are seen to be in excellent agreement over the considered temperature range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our chemical network includes collisional ionization, radiative recombination, photo-ionization and photodissociation processes, the formation of molecules and a multilevel model of atomic hydrogen. We found that the presence of a background flux photo-ionizes the gas and raises the gas temperature to ≥10 4 K. We found that for weak radiation fields (J 21 < 100), cooling due to H 2 decreases the temperature to at least 1000 K. For J 21 < 0.1, cooling by HD is important as well, leading to gas temperatures of ∼100 K. We note that the HD cooling function was recently revisited by Coppola et al (2011). However, they only find differences at high temperatures, where H 2 dominates the cooling.…”
Section: Discussionmentioning
confidence: 81%
“…Within the rate equations for the HD + isotope we have specifically included the spontaneous downward relaxation rates computed by Coppola et al [24]. Figure 7a compares the temporal evolutions of the first three levels of p-H into its j = 0 state, while the o-D + 2 system needs more than 6 s to reach the same dominant population of its ground rotational state.…”
Section: Computing the Relaxation Times From The Master Equationsmentioning
confidence: 99%